2014
DOI: 10.1016/j.seizure.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Hyperventilation during electroencephalography: Safety and efficacy

Abstract: HV is rarely associated with adverse events, but contributes to the diagnosis and classification of seizure disorders in an appreciable proportion of patients with epilepsy and non-epileptic attacks. These findings confirm that HV in selected patients is a valid activation technique in diagnostic EEG, where the potential benefits out weigh the risks, and also provide information that may assist the informed consent process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
56
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 33 publications
(40 reference statements)
10
56
1
2
Order By: Relevance
“…This is in accordance with previous studies on the diagnostic yield of HV during EEG [2,[7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in accordance with previous studies on the diagnostic yield of HV during EEG [2,[7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 93%
“…However, this is influenced by the low percentage of patients who had seizure or IEDs only during HV [11]. If we express the difference as percentage of the total number of patients who had seizures or IEDs only during HV, the difference between 3 and 5 min HV is 16% and 30%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Service evaluations have shown that, in patients referred for EEG with suspected PNES, 12/102 (11.8%) had a PNES elicited by hyperventilation and 15/133 (11.3%) had a PNES evoked by photic stimulation (Kane et al, 2014, Whitehead et al, 2016b). In one prospective study as many as 5/15 (33%) patients had a PNES during these activation procedures, when they were referred from a specialist outpatient clinic with probable PNES immediately after describing their symptoms to the doctor (McGonigal et al, 2002).…”
Section: Outpatient Synchronized Video-eegmentioning
confidence: 99%
“…EEG findings in COPD patients with encephalopathy/ intellectual impairment show higher occurrence of slow wave bands and lower occurrence of beta waves predominantly in the fronto-temporal region, secondary to hypoxemia & hypercapnia (9,10). Besides, a brief period of hyperventilation is also known to influence CNS by causing generalised increase in excitability helping to reveal latent epileptic foci if any, and hence is used in diagnosis of epilepsy by provoking epileptic discharges (11).…”
Section: Introductionmentioning
confidence: 99%